2015
DOI: 10.1007/s10792-015-0079-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser trabeculoplasty (SLT): 1-year results in early and advanced open angle glaucoma

Abstract: The purpose of this study was to examine the efficacy of selective laser trabeculoplasty (SLT) in eyes with early and more advanced stages of open angle glaucoma within 1 year of follow-up. Retrospective chart review in a consecutive series of patients treated by SLT to reduce intraocular pressure (IOP) or decrease number of topical medications in cases of discomfort and allergy. The cup-to-disc ratio of the optic nerve and the GSS 2 (glaucoma staging system 2) was used to differentiate between early (group 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…The success rates were 63% and 59.1% for early and advanced OAG, respectively. Results from this study allow clinicians to consider SLT as an alternative to higher-risk incisional therapies in advanced stages of OAG [13]. …”
Section: Indications and Efficacymentioning
confidence: 99%
“…The success rates were 63% and 59.1% for early and advanced OAG, respectively. Results from this study allow clinicians to consider SLT as an alternative to higher-risk incisional therapies in advanced stages of OAG [13]. …”
Section: Indications and Efficacymentioning
confidence: 99%
“…Da die SLT im Normalfall einen Zieldruckbereich zwischen 15 und 20 mmHg erreichen kann, ist sie kein Verfahren der ersten Wahl zur Behandlung fortgeschrittener Glaukome, für die oft ein Zieldruckbereich < 15 mmHg definiert wird. Bei kompensierten fortgeschrittenen Glaukomen kann sie aber bei reduzierter Verträglichkeit der medikamentösen Glaukomtherapie oder fehlenden Alternativen eingesetzt werden [18]. Bei Zeichen der Progression im Gesichtsfeld oder OCT sollte aber nach anderen Möglichkeiten der Drucksenkung gesucht werden.…”
Section: Indikationen (Glaukomform Glaukomstadium)unclassified
“…Schon bei der ALT war ein möglicher negativer Einfluss auf eine nachfolgende Trabekulektomie diskutiert worden und hat auch teilweise zu einer zurückhaltenden Position gegenüber der ALT beigetragen. Nach eigenen Erfahrungen scheint die SLT aber nicht das Vernarbungsrisiko einer nachfolgenden filtrierenden Chirurgie zu erhöhen [18].…”
Section: Wechselseitiger Einfluss Von Slt Und Glaukomchirurgischen Veunclassified
“…For instance, better results are usually observed in patients with POAG (33,37,(51)(52)(53)(54)(55)(56) , pseudoexfoliative glaucoma (31,40,57,58) , and higher baseline IOP (40,41,46,47) . A few isolated studies observed better results in eyes with thinner corneas (59) , with earlier disease stage (60) , and with higher refractive errors (52) . Conversely, the use of PGA before laser was associated with a decreased IOP-lowering response (61) , and SLT treatment had limited results in eyes with OAG receiving maximal-tolerable medical therapy (50,62) .…”
Section: Success Predictors Of Selective Laser Trabeculoplastymentioning
confidence: 99%